The level of implementation of COVID-19 measures in workplaces: Ideas for the future - Yüksel, Mümine; Sandal, Abdulsamet; Kalaycı, Defne; Yıldız, Ali Naci (Acta Medica, 2024)
Objective: The initial phases of Coronavirus Disease 2019 (COVID-19) pandemic required a wide range of preventive measures for various settings, including workplaces. The evaluation of workplace applications may guide all stakeholders for future similar outbreaks. This study aimed to evaluate the practice of Turkish occupational safety and health (OSH) professionals regarding COVID-19. Materials and Methods: The study included responses of OSH professionals who were members of three national organizations. Data were collected during the third peak of COVID-19 cases in Turkey. Results: Of 457 respondents, 92.6% reported at least one infected worker, and 12.7% reported mortality among workers due to COVID-19. Multiple regression analyses revealed an association with workplace size ≥250 for any COVID-19 infection among workers (OR=6.70, 95% CI:2.64–16.98, p<0.001) and for COVID-19 related mortality (OR=3.37, 95% CI:1.59–7.13, p=0.002). Moreover, working in governmental business enterprises was related to COVID-19 related mortality (OR=4.83, 95% CI:2.33–10.01, p<0.001). The mean number of available measures was significantly lower (p<0.001) in governmental business enterprises, the service sector, and workplaces with less than 250 workers. Conclusion: The results indicate a need for improvement in small- and large-sized workplaces, governmental business enterprises, and service sector workplaces.